CLINICAL MANAGEMENT OF DYSTOCIA DUE TO HYDROCEPHALUS IN A CROSSBRED COW. - SUCHITRA, B R; SAHADEV, S; RENUKARYADHYA, G J (The Indian Journal of Animal Reproduction, 2023)
Dystocia due to hydrocephalus in a crossbred cow and its clinical management has been reported.